Biological aphid control in loquat orchards - Soler E.; Juan N.; Toledo J. (First international symposium on loquat, 2003)
No parasitism by Aphidius was observed. Aphidoletes as a predator was the most abundant species (2-4 larvae per shoot). A generation lasts 3.5 weeks, hence the potential effects of predation were not observed at the end of July. A decrease in the aphid population was observed in both plots, the one studied and the control. The second species in terms of abundance was Scimnus (2-3 larvae per shoot). Additionally, 2-3 larvae from Crysopa per shoot along with eggs layers were observed. Larvae from sirphides and Propilea were observed too. According to the results the spread of beneficial insects should be done by mid May, which is the end of the harvest season and the season when the first aphid colonies are observed. The high cost of the biological alternative compared to the spraying of dimetoate makes this approach not viable at the present time.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)